Implementasi Kebijakan Merdeka Belajar: Antara Idealitas Konsep dan Realitas Lapangan di Berbagai Daerah Indonesia - Putri, Melyna Wijaya; Azizah, Reyhana Nur; Sofianisa, Ulyantika; Amirudin, Amirudin; Fitri, Tin Amalia (Universitas Islam Negeri Raden Intan Lampung, 2025)
This studi examines the implementation of the Freedom of Learning policy with a focus on the gap between the ideality of the concept and realities of its implementation in practice. The purpose of this study is to comprehensively analyze the effectiveness of the Merdeka Learning policy in achieving its ideal goals, identify supporting and inhibiting factors for implementation, and examine its implications on the quality of learning and education management. The research uses a qualitative approach with an exploratory case study design that was carried out in three representative provinces (East Java, South Kalimantan, and East Nusa Tenggara). Data were obtained through in-depth interviews, participatory observations, and analysis of policy documents with source triangulation techniques to ensure the validity of the results. The results of the study show that the implementation of the Merdeka Learning policy still faces various structural and cultural obstacles, such as disparities in resources between regions, limitations in teachers' pedagogical competence, and cultural resistance of bureaucracy in the school environment. This gap results in variations in the quality of learning and the effectiveness of policies between educational units. The discussion revealed that the success of implementation is highly dependent on regional policy support, transformational leadership, and continuous professional development. This study concludes that in order for the vision of Merdeka Learning to be realized substantively, an adaptive, collaborative, and contextual education management strategy is needed, while emphasizing the importance of evidence-based policies to ensure the sustainability of national education transformation.